PENGARUH RASIO SOLVABILITAS DAN RASIO PROFITABILITAS TERHADAP PERUBAHAN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Sev Rahmiyanti (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this research is to know the influence of the ratio of solvency and profitability ratios either partially or simultaneously to changes in Earnings at missing companies listed in Indonesia Stock Exchange. Solvency ratio that was tested was the Debt to Asset Ratio and theratio of tested profitability is Return On Equity. The population in this research is the 7 mising companies listed in Indonesia Stock Exchange. The selection of the sample using the method of purposive sampling. The total sample was 35 mising companies listed in Indonesia Stock Exchange during the period of 2014-2018 with 35 total research data. The data retrieved is secondary data by the method of documentation. Data analysis technique was done using classical assumptions test which include normality test, multicolinearity test, autocorrelation test and heteroscedasticity test, while the hypotheses test was done by using multiple regression analysis. The results of this study suggest that (1) there is a negative influence is not significant Debt to Assets Ratio to changes in Earnings at mining companies listed on the Indonesia Stock Exchange during the period of 2014-2018. (2) there is a significant positive influence on Return On Equity to changes in Earnings at mining companies listed on the Indonesia Stock Exchange during the period of 2014-2018. (3) there is a positive influence and significant Debt to Assets Ratio and Return On Equity to changes in Earnings at mining companies listed in Indonesia Stock Exchange during the period of 2014-2018. Based on the analysis of the regression test can be seen the value adjusted R square of 0,880 shows that Debt to Assets Ratio and Return On Equity was able to exert influence of 88% to changes in Earnings.